Produksi Tanaman Kangkung dan Ikan Lele dengan Sistem Akuaponik - Lukito Hasta Pratopo; Ahmad Thoriq (Paspalum: Jurnal Ilmiah Pertanian, 2021)
Kale and catfish are the most popular vegetables and fish in Indonesia. The production of these two commodities can be done using an aquaponics system. This study aims to determine the growth of water spinach plants and the survival of catfish in the aquaponic system. Plant growth parameters were measured every three days which included plant height, leaf width, leaf length, number of leaves and plant weight after harvest. The development of catfish that was observed every three days included the number of dead catfish and the weight of catfish measured every nine days. The data obtained were then tabulated and processed in graphical form and analyzed descriptively. The results showed The growth rate of kale planted in the aquaponic system includes plant height, leaf length, and leaf width, respectively, 2.51 cm / three days, 0.75 cm / three days and 0.24 cm / three days, while in kale plants (control) 1.30 / three days, 0.5 cm / three days, and 0.12 cm / three days, respectively. The yield of water spinach planted with the aquaponics system weighed 350 grams / pot, while the control water spinach was only 135 grams / pot. During 30 days of maintenance there was an increase in weight of catfish as much as 11.25 grams / head with the survival rate (SR) of catfish seeds by 93%.